Pengaruh Pemahaman Akuntansi, Tingkat Pendidikan dan Ukuran Usaha terhadap Kualitas Laporan Keuangan Umkm di Kecamatan Teluk Jambe Timur - Hilda Nurhidayah; Rohma Septiawati; Awaliawati Rachpriliani (Masyarakat Ekonomi Syariah Bogor, 2024)
This study aims to look at the effect of accounting understanding, education level and business size on the quality of MSME financial reports in the Teluk Jambe Timur sub-district. Questionnaires were used to obtain primary data for this quantitative research. In Teluk Jambe Timur sub-district, a sample of 93 MSMEs was selected using the puposive sampling technique. There are four types of tests in this study, namely, multiple linear regression analysis, instrument test, classical assumption test, and hypothesis testing. The findings of this study indicate that the three variables of accounting understanding, education level and business size have an impact on the quality of financial statements. This means that any variable used has the potential to affect how well MSMEs produce their financial reports.